2019
DOI: 10.3390/s19194342
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Motor Failure Time Using An Artificial Neural Network

Abstract: Industry is constantly seeking ways to avoid corrective maintenance so as to reduce costs. Performing regular scheduled maintenance can help to mitigate this problem, but not necessarily in the most efficient way. In the context of condition-based maintenance, the main contributions of this work were to propose a methodology to treat and transform the collected data from a vibration system that simulated a motor and to build a dataset to train and test an Artificial Neural Network capable of predicting the fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 45 publications
(93 reference statements)
0
31
0
1
Order By: Relevance
“…A methodology was proposed by Sampaio, G.S. et al [47] to treat and convert the collected data of vibration measurements from a vibration system that simulated a motor and to build a dataset in order to train and test an ANN model capable of predicting the future condition of the equipment, predicting when a failure can happen. The methodology involves the use of frequency and amplitude data by classifying the dataset and defining a way of calculating the vibrating system's failure time.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
See 1 more Smart Citation
“…A methodology was proposed by Sampaio, G.S. et al [47] to treat and convert the collected data of vibration measurements from a vibration system that simulated a motor and to build a dataset in order to train and test an ANN model capable of predicting the future condition of the equipment, predicting when a failure can happen. The methodology involves the use of frequency and amplitude data by classifying the dataset and defining a way of calculating the vibrating system's failure time.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…They have been successfully applied in several field of PdM applications. Some authors [10,30,[46][47][48][75][76][77]107,114,[118][119][120][121] focused on ANN ML algorithms. Some other authors [64][65][66][67]81,82,[84][85][86][87][88]90,116,117] studied RF technique.…”
mentioning
confidence: 99%
“…The downside is that it is a black box, meaning low interpretability. Sampaio et al [31] found that the MLP architecture worked effectively on non-linear and complex systems, furthermore it had great generalisation. On the downside, the convergence was found to be somewhat slow and that the model had a tendency to overfit.…”
Section: Categorymentioning
confidence: 99%
“…The term artificial neural network refers to a computational and machine learning technique [40][41][42][43]. One type of neural networks are multilayer perceptron neural networks (MLPs).…”
mentioning
confidence: 99%
“…Many ANN applications are related to renewable energy sources (different uses of ANN models for better energy production predictions). Research addresses for example the creation and use of ANNs to forecast solar radiation (the main problem for the best use of photovoltaic systems) and wind power forecasting [41,45,[57][58][59]. ANNs are applied for forecasting building energy usage and demand [42].…”
mentioning
confidence: 99%